Resurfacing Gender: A Typology of Conflict-Related Violence Against Women for the Northern Ireland Troubles - Swaine, Aisling (Violence against women, 2023)
The “Troubles” in Northern Ireland are often assumed to represent an outlier in respect of contemporary global discourse on conflict-related violence against women (CRVAW), and particularly “strategic rape.” CRVAW has neither commanded the narrative nor imagery of that conflict nor specifically recognized globally as part of women's experiences of it. A composite and comprehensive analysis of CRVAW for that context has been absent. Based on primary and secondary research, and analytically advanced through gender and critical harm theory, the article presents the first typology of CRVAW for the Northern Ireland Troubles. The article maps and evidences a range of gendered harms directly and indirectly resulting from the conflict enacted by state and nonstate actors. It argues that a resurfacing of gender is required to ensure current global debates on CRVAW are informed by a reconsideration of what constitutes “strategic” harm in armed conflict.